Perilous journey: a tour of the ubiquitin–proteasome system - Kleiger, Gary (2014)
Eukaryotic cells are equipped to degrade proteins via the ubiquitin–proteasome system (UPS). Proteins become degraded upon their conjugation to chains of ubiquitin where they are then directed to the 26S proteasome, a macromolecular protease. The transfer of ubiquitin to proteins and their subsequent degradation are highly complex processes, and new research is beginning to uncover the molecular details of how ubiquitination and degradation take place in the cell. We review some of the new data providing insights into how these processes occur. Although distinct mechanisms are often observed, some common themes are emerging for how the UPS guides protein substrates through their final journey.